Impact of split payment on financial liquidity of enterprises - Obrzeżgiewicz, Dawid (Wpływ split payment na płynność finansową przedsiębiorstw, 2019)
Maintaining financial liquidity forms the most important short-term goal of every enterprise. On the other hand, there are restrictions that reduce the liquidity level of economic entities, one of which is the taxation of turnover. As a rule, the goods and services tax should be neutral for the activities of business entities. However, in actual economic life, one may encounter situations in which the method of paying liabilities to the contractor, including VAT, leads to the deterioration of the company’s financial liquidity. The objective of this article is to analyze the impact of split payment on the company’s financial liquidity. The implementation of this objective will be supported by simulating the liquidity levels of the business entity with and without split payment
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 88-99